Research on the Methods of Exoplanet Detection and Discussion on Correlations and Flaws - Tian, Ruidong (Transactions on Computer Science and Intelligent Systems Research, 2024)
The search for exoplanets, particularly Earth-like planets, has garnered significant attention as potential second homes for human beings. Highlights of the urgency of finding alternative habitable planets due to the dire consequences of global warming and climate change on Earth. This underscores the importance of exoplanet research and the potential it holds for humanity’s future. This paper delves into the two fundamental methods used in the discovery of exoplanets include the transit method and the radial velocity method, accompanied by illustrative calculations. It further endeavors to establish a correlation between the observational data obtained through the transit method and the conditions that Earth-like planets might possess. Additionally, the paper acknowledges certain limitations and shortcomings that could compromise the accuracy of these two methods. Ultimately, the paper concludes that Earth-like planets, characterized by similar temperatures and compositions, tend to adhere to specific relationships in terms of their radii and masses. Overall, this paper contributes to the ongoing effort to find suitable habitable planets beyond the solar system, addressing both the methodologies and challenges associated with this exciting field of research.